Corynebacterium: abordagem genômica, relógio molecular e surgimento da patogenicidade - LIMA, Alyne Cristina Sodré (Universidade Federal do Pará, 2021)
We can identify microorganisms with pathogenic capacity or not within the same genus, through little information related to the time period of onset of pathogenicity, such as the genus Corynebacterium. The most relevant non-pathogenic species are: Corynebacterium glutmicum for its great importance in amino acid production, and the pathogenic species Corynebacterium diphtheriae producing diphtheria toxin, and Corynebacterium pseudotuberculosis leading causative agent of lymphadenitis caseosa. There is a lack of both epidemiological data and studies published in the state of Pará regarding the scenario of C. pseudotuberculosis in the northern region. Thus, the objective of this study was initially to disseminate the genome of the strain Cp05 C. pseudotuberculosis, as well as to include this and other specimens of isolates belonging to the genus Corynebacterium, in order to identify which genomic events are related to the emergence of the pathogenicity in Corynebacterium pseudotuberculosis, exploring the genomic plasticity within this genus. For the disclosure of the genome of the Cp05 C. pseudotuberculosis strain we used microbiological, molecular and biochemical tests. Using 64 genomes of different species of the genus Corynebacterium and Mycobacterium tuberculosis H37Rv, Nocardia sp. Y18 and Rhodococcus jostii RHA1 as outgroups for phylogenetic and molecular clock analysis. Testing the genes dnaA, dnaK, gyrb, recA, rpoB and 16S rRNA, for comparative genomic analysis from three species: C. pseudotuberculosis, C. diphtheriae and C. glutamicum. These genomes had the ortholog genes calculated in PGAP v.1.2.1, and species specific genes were analyzed in Blast2GO v.5.0 software to determine cell compartments, molecular functions and biological processes. To determine differences between genomic characteristics, variance analysis (p <0.05) was compared: genome size, number of genes and gene density. In the Bayesian phylogenetic tree obtained, the pathogenic species C. pseudotuberculosis, C. diphtheriae and C. ulcerans grouped. A second grouping of pathogenic species was formed by C. kutscheri, C. matruchotii and C. mustelae, close to the C. pseudotuberculosis clade. C. glutamicum has formed a non-pathogenic clade that includes C. crubilactis, C. allunae, C. deserti and C. efficiens. C. glutamicum was one of the nonpathogenic species most closely related to the pathogenic species of the C. pseudotuberculosis clade. Divergences between Corynebacterium species have been observed every 5,000 years, in addition to the first species of this genus being free-living bacteria and undergoing adaptation to different hosts. Comparative genomic analysis of the three Corynebacterium species allowed an understanding of the genomic evolution of pathogenic corynebacteria, given the sharing of 911 genes from orthologists. Obtaining the protein sequence of the genes and the analysis of these sequences presented the main terms of gene ontology, which were oxidation reduction process; ATP and DNA binding; and integral component of the membrane. Sequencing of new strains is necessary, because with more specimens the better the understanding of the evolution of this genus, the better the understanding of C. pseudotuberculosis pathogenicity, which here can be confirmed evolutionarily associated with animal domesticity, genome size reduction and prioritization of essential genes for maintaining cell life.